Measuring Fatigue in TBI: Development of the TBI-QOL Fatigue Item Bank and Short Form. Issue 5 (September 2019) - Kisala, Pamela A.; Bushnik, Tamara; Boulton, Aaron J.; Hanks, Robin A.; Kolakowsky-Hayner, Stephanie A.; Tulsky, David S.
Abstract : Objective: To develop a traumatic brain injury (TBI)-specific, item response theory (IRT)-calibrated Fatigue item bank, short form, and computer adaptive test (CAT) as part of the Traumatic Brain Injury-Quality of Life (TBI-QOL) measurement system. Setting: Five TBI Model Systems rehabilitation centers in the US Participants: Adults with complicated mild, moderate, or severe TBI confirmed by medical record review. Design: Cross-sectional field testing via phone or in-person interview. Main Measures: TBI-QOL Fatigue item bank, short form, and CAT. Results: A total of 590 adults with TBI completed 95 preliminary fatigue items, including 86 items from the Patient-Reported Outcomes Measurement Information System (PROMIS) and 9 items from the Quality of Life in Neurological Disorders (Neuro-QOL) system. Through 4 iterations of factor analysis, 22 items were deleted for reasons such as local item dependence, misfit, and low item-total correlations. Graded response model IRT analyses were conducted on the 73-item set, and Stocking-Lord equating was used to transform the item parameters to the PROMIS (general population) metric. A short form and CAT, which demonstrate similar reliability to the full item bank, were developed. Test-retest reliability of the CAT was established in an independent sample (Pearson's r and intraclass correlation coefficient = 0.82 [95% confidence interval: 0.72-0.88]). Conclusions: The TBI-QOL Fatigue item bank, short form, and CAT provide rehabilitation researchers and clinicians with TBI-optimized tools for assessment of the patient-reported experience and impact of fatigue on individuals with TBI. Abstract : Supplemental Digital Content is Available in the Text.